2016
DOI: 10.3390/ijms17121989
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Interactions Control Structural and Thermal Properties of Regenerated Tri-Component Blended Films

Abstract: With a growing need for sustainable resources research has become highly interested in investigating the structure and physical properties of biomaterials composed of natural macromolecules. In this study, we assessed the structural, morphological, and thermal properties of blended, regenerated films comprised of cellulose, lignin, and hemicellulose (xylan) using the ionic liquid 1-allyl-3-methylimidazolium chloride (AMIMCl). Attenuated total reflectance Fourier transform infrared (ATR-FTIR) analysis, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The study found that the mechanical strength of the biocomposites was evidently depending on the contents of lignin, starch and cellulose, resulting from the mutual supplement among different components. High gas barrier ability and great thermal stability were clearly observed in the biocomposites [105]. Holo-cellulose and acid insoluble lignin of Pecan nutshell fiber were utilized as reinforcements of PLA-based bioplastics.…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…The study found that the mechanical strength of the biocomposites was evidently depending on the contents of lignin, starch and cellulose, resulting from the mutual supplement among different components. High gas barrier ability and great thermal stability were clearly observed in the biocomposites [105]. Holo-cellulose and acid insoluble lignin of Pecan nutshell fiber were utilized as reinforcements of PLA-based bioplastics.…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…Due to its high degree of crystallinity, the materials are extremely stable through hydrogen bonding [61]. These materials contain no antigenic properties, which makes them biocompatible as well as eco-friendly [62][63][64].…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…The regenerated biomass films were prepared by using a modified version of the protocol seen in previous literature [ 8 , 32 ]. To increase the compatibility of the GO sheets with lignin and to increase its adhesion capabilities, GO was reduced with 0.005 g Vitamin C in 1 mL water and then heated to 50 °C for 24 h. After that, it was rinsed five times with water in a centrifugation process to remove the remaining Vitamin C. After which, the rGO was filtrated by pouring it through cellulose filter paper and then dried for 24 h. The AMIMCl was placed in a test tube (approximately 90 w / w ) and heated in oil at 90 °C, at which point the biomass components (lignin, xylan and cellulose paper with rGO approximately) were added to top 11 w / w .…”
Section: Methodsmentioning
confidence: 99%
“…There is also covalent bonding among the components, such as an ester bond between lignin and hemicellulose, and ether bonds between cellulose and lignin [ 6 , 7 ]. Lignin is a component that fills the spaces between hemicellulose and cellulose, where it acts as a resin that holds the lignocellulosic matrix together [ 8 ]. These natural interactions enable the formation of hierarchical fibers for which its properties depend on material structural complexity, molecular distribution and composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation